O ciclo «natureza e ecologia» na literatura de cordel brasileira - Carlos Nogueira (Caravelle)
This article is a research dealing with the naturist and ecological thinking of Brazilian cordel which, linking different fields such as nature, environment, religion, techniques, science, teaching, citizenship and denouncing the disparities and injustices suffered by people and by living or lifeless creatures, has elaborated a whole cycle to which literary critic has not paid enough attention.